14 Bissat, an international student experience - Stancato, Fernando; Mangili Jr., José Fernando; Tribess, Arlindo [UNESP]; Prodsan, Yulian (American Institute of Aeronautics and Astronautics (AIAA), 2005)
On August 2003 an accident with the Brazilian Launcher, VLS, destroyed the UNOSAT (www.space.unopar.br) that was the first Brazilian University Undergraduate Student nano satellite. Three months latter an invitation to put some of the UNOSAT hardware inside an Ukrainian university micro satellite, UMS, appeared. The UMS satellite is been developed by a group of students of the Dnepropetrovsk National University, Ukraine, with the help of young engineers of the Spacecraft Design Office of Yuzhnoye. In this way both UMS and a new Brazilian nanosatellite 14 Bissat project started, coordinated by two doctorate students with undergraduates. The name of 14 Bissat is to commemorate the 100 year of the flight of the first airplane by the Brazilian Santos Dumont in Paris and is an acronym of Brazilian International Student Satellite. Soon a new team of students of the Escola Politécnica and Universidade Norte do Parana, Brazil, was formed and discussion on the 14 BISSAT preliminary design began. After the exchange of basic information of Brazilian/Ukranian sides, it was decided that the same configuration used on the UNOSAT could be used with small modifications. The Brazilian students had to do a much more compact design as the volume was going to be four time smaller. As the previous satellite, it was going to download a voice message and a packet of telemetry. As the information is going to be sent by amateur radio band a collaboration was gotten by an Brazilian amateur radio association called ABRASAT (www.abrasat.org). The different project parts were divided among the thirteen students: structure, radio link, solar panels, energy controller module, telemetry and instrumentation. They were also responsible for the systems tests, integration and follow final tests. After nine months the students did the design, integration and tests of the 14 BISSAT. Besides putting on practice the disciplines of their respective courses, new skills was gotten as international information exchange using internet resources as emails and chats. The team had to overcome a series of difficulties as lack of experience, resources, bibliography, and time. But with some indigenous ideas the students and teachers managed to finish the nanosatellite. It is explained an aerospace management procedure that contributed to keep to project schedule. It was used only non space qualified parts and a simple qualification procedure was followed. International collaboration was a key factor for the success in the preliminary project phase and in construction. Innumerous benefits for the students arose from the program: capacity to overcome academic obstacles, responsibility, high quality and reliable project/manufacture, teamwork and international experience. Nowadays another group of the Metropolitana-IESB is doing the flight module that is expected to be launched in 2006.